1997
DOI: 10.2307/1592164
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Coccidiosis in Outbred Chickens Elicited by Gamma-Irradiated Eimeria maxima

Abstract: In an effort to develop an attenuated coccidiosis vaccine against coccidiosis, we exposed Eimeria maxima oocysts to an optimum dose of gamma irradiation (17 kRad) that does not affect sporozoite invasion of the intestinal mucosa but does prevent asexual parasite development. Irradiated E. maxima oocysts were suspended in gelatin slabs and placed in battery cages for ingestion by 1-day-old chickens. Separate groups of chickens were given gelatin slabs containing nonirradiated E. maxima oocysts or were inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…As described above, the previously published data suggest that various developmental stages of parasite can induce substantial immunity. Interestingly, the previous study indicated that larger doses of irradiated E. maxima were required to induce immunity in chickens and suggested that dose of antigen might be important, where the important protection-inducing antigen would affect in the successive developmental stages [11]. Our data allow to put a similar interpretation on E. pragensis but also suggests that the proportions of different developmental stages of parasite may not dramatically influence the development of immunity.…”
Section: Discussionsupporting
confidence: 63%
“…As described above, the previously published data suggest that various developmental stages of parasite can induce substantial immunity. Interestingly, the previous study indicated that larger doses of irradiated E. maxima were required to induce immunity in chickens and suggested that dose of antigen might be important, where the important protection-inducing antigen would affect in the successive developmental stages [11]. Our data allow to put a similar interpretation on E. pragensis but also suggests that the proportions of different developmental stages of parasite may not dramatically influence the development of immunity.…”
Section: Discussionsupporting
confidence: 63%
“…Effects of gamma irradiation have been studied with Eimeria maxima in an effort to develop an attenuated coccidiosis vaccine [8,10] and also with C. parvum oocyst viability to assess its effectiveness in the prevention of C. parvum infection [15]. In our study, to confirm that the immunity observed in IL‐12 knockout mice challenged with C. parvum oocyst was due to the primary oocyst infection, we exposed C. parvum oocysts to similar doses of y‐irradiation used for E. maxima that have been shown to affect sporozoite invasion of the intestinal mucosa but does prevent asexual parasite development following irradiation (17 kRad).…”
Section: Resultsmentioning
confidence: 91%
“…[2001] and Williams [2001], respectively; supported by this study). The influence of the initial dose size or number on immune protection against subsequent homologous challenge with Eimeria acervulina , Eimeria brunetti , E. maxima or Eimeria tenella infection has been described (Hein, 1975;Lillehoj, 1988;Jenkins et al ., 1997) but remains less clearly defined in the face of challenge by a heterologous strain (Smith et al ., 2002). That initial doses of five or 10 oocysts of E. maxima proved capable of inducing a high degree of immunity to homologous challenge supports previous reports of the potent immunogenicity of this parasite (Rose & Long, 1962;Lee & Fernando, 1978;Smith et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%